Framing the Collective Memory of the 1990s as a Legitimation Tool for Putin's Regime - Malinova, Olga (Problems of post-communism, 2021)
The article reveals how a sharp contrast between the "turbulent 1990s" and the "stable 2000s" was constructed and exploited by Vladimir Putin and Dmitry Medvedev for shoring up the regime. Using a qualitative content analysis, I demonstrate how Putin's power was legitimized through three discursive mechanisms of re-presenting the recent past: the coining of buzzwords that became symbolic descriptors of the 1990s; the populist framing of the regime's policies; the composition of narratives about the immediate post-Soviet years. Constructed largely in the early 2000s, the negative framing of the Yeltsin decade became central to the official legitimizing discourse of Putin's regime.